1984
DOI: 10.1128/aac.26.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Safety of prolonged administration of rimantadine hydrochloride in the prophylaxis of influenza A virus infections in nursing homes

Abstract: We evaluated the safety of rimantadine hydrochloride (RH) prophylaxis in a double-blind, placebocontrolled trial in three nursing homes during a community epidemic of influenza A (H3N2). Although daily monitoring of the 35 participants revealed an association between RH administration (100 mg twice a day) and the development of nausea and anxiety (P < 0.05), these and other potential side effects were transient and were rarely considered to be clinically significant. Serum RH levels measured at the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…In contrast, the observed peak levels in serum for chronically ill, elderly nursing-home residents (12) taking 100 mg of rimantadine twice daily ranged from 634 to 2,602 ng/ml at steady state (mean = 1,159 ng/ml). This study (12) also found more cases of nausea and anxiety among rimantadine recipients compared with placebo recipients. The medical conditions of the patients may have involved some degree of renal impairment.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, the observed peak levels in serum for chronically ill, elderly nursing-home residents (12) taking 100 mg of rimantadine twice daily ranged from 634 to 2,602 ng/ml at steady state (mean = 1,159 ng/ml). This study (12) also found more cases of nausea and anxiety among rimantadine recipients compared with placebo recipients. The medical conditions of the patients may have involved some degree of renal impairment.…”
Section: Discussionmentioning
confidence: 75%
“…One female (subject 12) developed an acute purulent bronchitis on day 16 of the study that was associated with premature ventricular contractions. She was treated with oral antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is evidence that the therapeutic index for rimantadine is wide. Patriarca et al (8) reported no correlations between adverse experiences and rimantadine concentrations in serum which ranged from 634 to 2,600 ng/ml 3 to 4 h after the last dose of a 100-mg-twice-daily 10-day regimen. Similarly, there were no correlations between rimantadine concentrations in serum in excess of 1,000 ng/ml and adverse events in studies conducted by the Rochester group (R. Betts and R. Dolin, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetic data are not available for most of the compounds used in the study described in this report, but both amantadine and rimantadine have been well studied. Steady-state levels in serum of 0.5 to 1.0 g ml Ϫ1 (2.5 to 5.0 M) and above and serum half-lives of between 24 and 36 h have been widely reported (1,2,9,14,26). In addition, the drugs readily gain access to the central nervous system (22).…”
Section: Discussionmentioning
confidence: 99%